2015
DOI: 10.1007/s00240-015-0760-x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde intrarenal surgery for the treatment of renal stones: is fluoroscopy-free technique achievable?

Abstract: The aim of this study was to present the safety and efficacy of retrograde intrarenal surgery (RIRS) procedures that minimize the intraoperative radiation exposure. The totally endoscopy-guided RIRS technique included the following steps: (a) preoperative assessment of pelvicaliceal system anatomy and stone characteristics, (b) thorough evaluation of the ureters by rigid ureteroscopy, (c) a step-wise approach of introducing the ureteral sheath, (d) gathering stones in the more accessible renal calyx before fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
2
19
0
2
Order By: Relevance
“…In a recently published paper, the authors evaluated a fluoroscopy-free RIRS technique for renal stones and achieved stone-free status in 95.7% of the patients. [10] In that study, the authors defined the stone-free status as the absence of any fragments or residual fragments <2 mm in diameter on plain abdominal radiography or ultrasound (US) imaging. It is well known that CT, which was used in the present study to evaluate the success rate, is more sensitive for detecting renal stones than both US and plain radiography (96.6%, 45% and 44-77%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published paper, the authors evaluated a fluoroscopy-free RIRS technique for renal stones and achieved stone-free status in 95.7% of the patients. [10] In that study, the authors defined the stone-free status as the absence of any fragments or residual fragments <2 mm in diameter on plain abdominal radiography or ultrasound (US) imaging. It is well known that CT, which was used in the present study to evaluate the success rate, is more sensitive for detecting renal stones than both US and plain radiography (96.6%, 45% and 44-77%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Therefore, fluoroscopy-free techniques and radiation exposure-minimising techniques have become popular in the field of urology. [6][7][8][9][10] The present study aimed to determine the outcomes of our fluoroscopyfree RIRS technique and evaluate its safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in order to decrease the exposed dosage, decreased use of fluoroscopy or fluoroscopy-free techniques have been reported. Peng et al [8] evaluated the fluoroscopy-free RIRS in 144 patients with a mean stone dimension of 1.4±0.4 cm. They required fluoroscopy in only 1 patient who had a duplicated collecting system.…”
Section: Rirs and Fluoroscopymentioning
confidence: 99%
“…In another study by Peng et al . [12] they showed that retrograde intrarenal surgery is feasible without fluoroscopy. In that study 95.7% of stone-free rate was achieved over 1 month with minimal complication.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Peng et al . [12] using low radiation fluoroscopy, they were able to keep the total fluoroscopy time 0–35 s with excellent success and low complications rate. In another study by Scarpa et al .,[13] they performed successful rigid ureteroscopy in 15 pregnant patients with the help of ultrasound only.…”
Section: Discussionmentioning
confidence: 99%